Appendix: Conodonts from the Permian-Triassic boundary beds at Kap Stosch, East Greenland - Walter C., (Meddelelser om Grønland, 2024)
Six hundred eighty-eight identifiable conodont elements were recovered from 37 of 68 samples that were collected for this purpose in 1967 by TEICHERT & KuMMEL. All samples are from Upper Permian and Lower Triassic strata, and come from seven localities in the vicinity of Kap Stosch, the northernmost end of the Hold with Hope Peninsula, East Greenland. Samples are precisely located in sections that are described elsewhere by TEICHERT & KuMMEL (1976). Conodont elements in the 37 productive samples studied represent the species identified and enumerated in Table I. The conodont species compose two distinct faunas, an older one with Neogondolella rosenkrantzi (BENDER and STOPPEL) and a younger one with Anchignathodus typicalis SWEET. I comment on the stratigraphic significance of these faunas separately in the following paragraphs.